2012
DOI: 10.1111/j.1468-2435.2012.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Migratory Contacts and Remittances Contribute to Reconciliation and Reconstruction in Rwanda?

Abstract: Migratory contacts may have a positive or a negative influence on local processes of reconciliation and reconstruction. However, their impact on individual attitudinal and behavioural attributes remains a largely underexposed topic. Migrants from post‐conflict Rwanda maintain substantive contacts with their relatives through social networks and the resources that they send. Reconstruction and reconciliation programmes in post‐conflict Rwanda heavily rely on these migratory contacts. We explore the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Organisational social capital significantly influence the rural households' access to and amount of credit facilities available from different sources (Balogun, Yusuf, Omonona & Okoruwa, 2011), and Caarl, Fransen & Ruben's (2013) study confirmed the positive impact on welfare, of remittances on beneficiary households, particularly in urban areas. Remittances are a type of extra income, which flowed through informal channels -hand deliveries and couriering within family networks based on trust and solidarity (Fransen, 2015).…”
Section: Social Capital and Household Welfarementioning
confidence: 77%
“…Organisational social capital significantly influence the rural households' access to and amount of credit facilities available from different sources (Balogun, Yusuf, Omonona & Okoruwa, 2011), and Caarl, Fransen & Ruben's (2013) study confirmed the positive impact on welfare, of remittances on beneficiary households, particularly in urban areas. Remittances are a type of extra income, which flowed through informal channels -hand deliveries and couriering within family networks based on trust and solidarity (Fransen, 2015).…”
Section: Social Capital and Household Welfarementioning
confidence: 77%
“…They found that within the Diaspora Dialogue project in Portland, Oregon, diaspora members felt strong about their ability to influences circumstances within their home countries. Additionally, Caarls, Fransen, and Ruben (2012) collected survey data from 568 households within the Huye District of Rwanda to determine how the family relationships between those living inside and outside of country impacted their beliefs about reconciliation. The authors found that continued relationships with family outside of Rwanda contributed to participants in reconciliatory actives and attitudes.…”
Section: Post-genocidal Notions Of Ethnicity: Connections Between Thementioning
confidence: 99%
“…However, within this literature, it is also acknowledged that most refugee crises do not result in refugee militarization (Adelman 1998; Salehyan and Gleditsch 2006, 361; Stedman and Tanner 2003) and that diasporas also engage in peaceful politics (Lyons 2007; Salehyan 2009, 34). At the same time, new research has begun to document the peace-promoting impact of migrants in various phases of armed conflict and conflict resolution (Brinkerhoff 2006; Caarls, Fransen, and Ruben 2013; Cochrane 2007; Cochrane, Baser, and Swain 2009; Horst 2008; Orjuela 2008; Smith and Stares 2007). Nevertheless, civil war research still largely conceives of migrants in terms of the risks they pose, a view reflected in recent reviews of the literature (Blattman and Miguel 2010, 29-30; Fearon 2010, 41; Golan and Gal 2009, 127; Hoeffler 2012, 23).…”
Section: Review Of Previous Researchmentioning
confidence: 99%